Computational biology: where nature meets technology / Ts Faikah Awang @ Ismail and Ts Mohamad Shahrimi Hashim - Awang @ Ismail, Faikah; Hashim, Mohamad Shahrimi (UiTM Cawangan Negeri Sembilan, 2023)
As we know biology is a study of nature and before computer analysis become a norm, most of the data gathered were analysed manually and needed to be carefully organized to ensure the quality of the data and the reporting process are less tedious. Nowadays, with the technology of artificial intelligence and supercomputer, data gathering, analysis and reporting become more manageable and accessible for benefit of humankind. The field of study that specializes in those data analysis was known as Computational Biology. Computational Biology is where the intersection of computer science, biology, chemistry, genetics, and big data analysis. It all began in the early 1970s when basic artificial intelligence was developed to create the neural network model for the human brain to generate new algorithms. Data that are being gathered helps the researchers to evaluate and compare the large data set to predict the variable in human brain function. The best use of computational biology began in 1990 known as the “Human Genome Project” and by 2003, the project had mapped around 85% of the human genome. This becomes the main big data analysis to predict human evolution. This is very important as it helps to gather the information for genetic therapy, especially for a disease that is classified as hereditary diseases such as neurological disease and cancer.